2009
DOI: 10.1007/s00441-009-0790-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal classes in the corticoid complex of the telencephalon of the strawberry finch, Estrilda amandava

Abstract: The present study, based on neurohistological techniques (Nissl-staining, Golgi-impregnation), focuses on the cytoarchitecture of the corticoid complex in the strawberry finch, Estrilda amandava. This complex in birds occupies the dorsolateral surface of the telencephalic pallium and remains subdivided into an intermediate corticoid area (CI) and a dorsolateral corticoid area (CDL). The CDL in the strawberry finch is a thin superficial part of the caudal pallium adjoining the medially situated hippocampal form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 60 publications
(81 reference statements)
4
14
0
Order By: Relevance
“…The pyramidal neurons accounting for at least 70% of the total neocortical population in mammals form the principal element in neocortical circuit. The evolutionary trend of pyramidal neurons' development can be traced right from "extraverted" neurons observed in amphibian pallium; pyramid-like neurons in reptilian cortex (Luis de la Iglasia and Lopez Garcia, 1997;Srivastava et al, 2007Srivastava et al, , 2009b; in hippocampus of homing pigeon, chick (T€ omb€ ol et al, 2000); corticoid complex in strawberry finch (Srivastava et al, 2009a) to the well developed neocortical elements referred by Cajal as "psychic cells" (Nieuwenhuys, 1994). The different aspects of pyramidal cell microanatomy may influence different aspects of cellular, and systems function (Elston and DeFelipe, 2002;Ha€usser and Mel, 2003;Segev et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The pyramidal neurons accounting for at least 70% of the total neocortical population in mammals form the principal element in neocortical circuit. The evolutionary trend of pyramidal neurons' development can be traced right from "extraverted" neurons observed in amphibian pallium; pyramid-like neurons in reptilian cortex (Luis de la Iglasia and Lopez Garcia, 1997;Srivastava et al, 2007Srivastava et al, , 2009b; in hippocampus of homing pigeon, chick (T€ omb€ ol et al, 2000); corticoid complex in strawberry finch (Srivastava et al, 2009a) to the well developed neocortical elements referred by Cajal as "psychic cells" (Nieuwenhuys, 1994). The different aspects of pyramidal cell microanatomy may influence different aspects of cellular, and systems function (Elston and DeFelipe, 2002;Ha€usser and Mel, 2003;Segev et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The histological structure of dorsolateral corticoid area (DCA), the hippocampus complex and the piriform cortex, in the (C. l. domestica) similar to (12) who studying on Strawberry finch (Estildamandava), it was found to be similar to the current study. The corticoid complex in birds is similar to the lateral cortex of (the reptiles and the mammalian) cortex as indicated by Srivastava (12).…”
Section: Discussionmentioning
confidence: 62%
“…The corticoid complex (CC) of birds has been supposed to participate in spatial memory (Atoji & Wild, 2005; Colombo et al, 2001). The CC of birds is present at the dorsolateral surface of the telencephalic pallium which can be divided into two subregions: an intermediate corticoid (CI) area adjacent to the parahippocampal area (APH) and a dorsolateral corticoid (CDL) area (Montagnese et al, 1996; Srivastava, Chand, et al, 2009; Srivastava et al, 2014). At the caudal most level the CI and hippocampal complex (HCC) progressively disappear, while the APH remains visible and limited laterally by the CDL in finches (Montagnese et al, 1996; Srivastava, Chand, et al, 2009) and Indian house crow (Srivastava et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The CI could constitute a zone of transition between the HA and HCC based on neuronal types (Montagnese et al, 1996; Srivastava, Chand, et al, 2009; Srivastava et al, 2014) and the distribution of neurotransmitters (Krebs et al, 1991), neuropeptides (Erichsen et al, 1991), zinc, and calbindin (Montagnese, Geneser, et al, 1993; Montagnese, Krebs, et al, 1993). The morphological characteristics of neuronal types have been studied by different researchers in the CC of the strawberry finch (Srivastava, Chand, et al, 2009), Indian house crow (Srivastava et al, 2014), and hippocampal and CC of the zebra finch (Montagnese et al, 1996). All of these studies have shown the presence of dominant multipolar neurons, pyramidal neurons, and stellate neurons in both food storing and nonfood storing birds (Montagnese et al, 1996; Srivastava, Chand, et al, 2009; Srivastava et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation